Development of culinary tourism based on tourist's perception and experience in Balikpapan City - Gozali Gozali; Tuwuh Adhistyo Wijoyo (Jurnal Pariwisata Pesona, 2022)
Culinary tourism has recently become the most dynamic and expansive global trend and continues to experience positive developments in many countries, one of which is Indonesia. However, the existence of food-related tourism often ignores the expectations of tourists themselves and tends to operate without collaboration with various parties. In fact, culinary tourism relies on mutually beneficial multi-stakeholder policies and cooperation tailored to market demands. This paper aims to analyze the perceptions and experiences of tourists in the development of culinary tourism which is still neglected in the literature. Data collection was carried out through a survey by distributing questionnaires to 109 local tourists who had visited or were currently visiting five culinary tourism destinations in the city of Balikpapan (Wisata Kuliner Taman Bekapai, Wisata Kuliner Pasar Segar, Wisata Kuliner Coto Makassar, Wisata Kuliner Ruko Bandar Dan Wisata Kuliner Pantai Melawai). The data that has been obtained were analyzed descriptively (arithmetic average) with the help of SPSS 21.0. The results of the analysis show that tourists' perceptions of local food that characterize culinary tourism destinations are (x̅ = 4.53, SD = 0.58), and the average tourist experience of pleasant food in terms of taste is (x̅ = 4.34, SD = 0.65). In this study, both of them got the highest average value of the 18 items tested. This study contributes to the culinary tourism development literature based on tourist expectations and contributes practically to stakeholders in the field of tourism and culinary tourism in making optimal use of their resources.